2006
DOI: 10.1258/135763306777889118
|View full text |Cite
|
Sign up to set email alerts
|

Four years' experience with antepartum cardiotocography using telemedicine

Abstract: We reviewed the first four years of experience with telemonitoring of patients with high-risk pregnancies. Nine peripheral units (eight in Campania, a region of south Italy, and one in Hungary) recorded cardiotocographic traces and transmitted them via modem to an operations centre at the University 'Federico II' in Naples, where the computerized analysis was performed. The medical report was returned to the peripheral unit via fax or email. Four thousand and twenty one traces were recorded: 2674 (67%) from 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…On the technical side, a recent work by Jezewski et al [38] demonstrated the equivalence of abdominal FECG and Doppler Ultrasound (CTG) methods, in terms of ability of clinical parameters to distinguish between normal and pathological fetuses. This fact supports the remote use of advanced signal processing methods already developed for CTG analysis antepartum in the clinical center deputed to the tele-monitoring service [13]. Moreover, a recent review paper on telemonitoring in obstetrics [39] shows "the added value, for both mother and child, of telemonitoring used in prenatal follow-up program" and suggests that it can be recommended for pregnant women at risk.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…On the technical side, a recent work by Jezewski et al [38] demonstrated the equivalence of abdominal FECG and Doppler Ultrasound (CTG) methods, in terms of ability of clinical parameters to distinguish between normal and pathological fetuses. This fact supports the remote use of advanced signal processing methods already developed for CTG analysis antepartum in the clinical center deputed to the tele-monitoring service [13]. Moreover, a recent review paper on telemonitoring in obstetrics [39] shows "the added value, for both mother and child, of telemonitoring used in prenatal follow-up program" and suggests that it can be recommended for pregnant women at risk.…”
Section: Discussionmentioning
confidence: 63%
“…Although pregnancy in itself is not a pathology, the fetal condition should be monitored as often as possible in order to prevent unfavorable outcomes. The literature shows that pregnant women could highly benefit by a remote monitoring service that is particularly effective for those patients and also helps in achieving a more efficient use of the health care [13,14]. This is because the reduction of in-or out-stays for patients only undergoing routine examinations mitigates the shortages of beds in hospitals and reduces any related management costs.…”
Section: Introductionmentioning
confidence: 99%
“…Most commonly, telemonitoring is used for the distant surveillance of patients with chronic disease, such as chronic heart failure, chronic obstructive pulmonary disease and diabetes mellitus. However, fetal heart rates and the level of activity of elderly people have also been monitored [4,18]. The same type of technology may also be used to record a patient's subjective response to specific pre-set questions about their health [5].…”
Section: Clinical Use Of Telemonitoringmentioning
confidence: 99%
“…Data about the first years' operation of the project have been published. 10,11 The TOCOMAT network connects eight remote units located in small hospitals and consulting rooms of Campania, a region in the south of Italy. The operation center is located in Naples, the regional capital, at the University "Federico II."…”
mentioning
confidence: 99%